Effect the Mind-Blowing Strategy In Endowing Speaking Skill On Fourth Grade studentsIn Science - Sultan, Manal; Jmal, Mohammad (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research aimed to explore impact of using mind-blowing strategy in endowing speaking skill on Fourth Grade pupils in science, to achieve the research goals a random sample was taken of 94 pupils of Fourth Grade in Lattakia Governate, (35) of which for the control group and 29 for the experimental group, It was applied on the experimental group each of skills remarking card and the test of speaking skills performance. The research reached the following results: -There was an impact of using mind-blowing strategy in endowing speaking skill on Fourth Grade pupils in science according to the modified gaining on each of skills remarking card and the test of speaking skills performance. -There were differences in the mean degrees of both the experimental and control groups in the post applying on each of skills remarking card and the test of speaking skills performance in favor of the experimental group’s degrees. -There were no differences that have statistical indication in the mean degrees of scoring of the Fourth Grade pupils of Basic Teaching (males and females) of the experimental group in post applying on each of skills remarking card and the test of speaking skills performance. -There were differences in the mean degrees of scoring between the pupils in prior and post test in favor of the marks of post applying pupils on each of skills remarking card and the test of speaking skills performance. The research offered several recommendations, the most important is the necessity of doing continuous training courses for the teachers to give them sight into how to develop oral communication skill and make student gain oral communication skills in schools.